(untitled) (Mandaluyong City, Philippines, 2007)
Contents: ADB and how it works; Spotlight on the environment, social development and governance; ADB's corporate footprint; Index to the global reporting initiative indicators.
Keywords: Sustainable development,Phát triển bền vững; Evaluation,Đánh giá; Asia,Châu Á